Kebijakan Formulasi Hukum Pidana terhadap Praktik Nikah Siri dan Poligami Tanpa Izin Berdasarkan Undang-Undang Nomor 1 Tahun 2023 - Muhamad Ramdhan; Abdul Kodir Alhamdani; Yudi Wahyudin; Mumu Fahmudin; Mohammad Husni Mubarok (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
The practice of unregistered marriage (nikah siri) and polygamy without court permission remains a persistent legal problem in Indonesia, causing serious consequences for the legal protection of women and children. This study aims to analyze the criminal law formulation policy against nikah siri and unauthorized polygamy practices based on Law Number 1 of 2023 on the new Criminal Code (KUHP), compare it with the formulation under the old Criminal Code, and evaluate its alignment with the objective of legal protection for women and children. This research employs a normative legal research method with statutory, conceptual, and comparative approaches, analyzing primary and secondary legal materials qualitatively. The results reveal three main findings: first, the formulation policy under the old Criminal Code contains structural weaknesses, including the absence of explicit criminal sanctions in the Marriage Law, the complaint-based nature of the offense that limits prosecution, inconsistent interpretation of Article 279 among law enforcement officers, and the misapplication of criminal provisions against perpetrators of secret polygamy; second, Law Number 1 of 2023 brings significant reforms through a more comprehensive reformulation of marriage offenses, more precise elements of criminal acts, a more flexible sanction system, and the integration of restorative justice principles; third, the formulation policy still requires strengthening in terms of protecting the rights of women and children, as criminal approaches alone are insufficient without synergy with administrative policies and community empowerment. This study concludes that the criminal law formulation policy in the new Criminal Code must be understood as an instrument for achieving substantive justice oriented toward the protection of life, lineage, and property as required by the principles of maqashid syari'ah.